2023 epidemic dengue fever outbreak: the experience of a pediatric hospital in the City of Buenos Aires - Ordoñez, Carolina (2025)
Introduction. Dengue is a viral infection that may be asymptomatic or include severe manifestations. This study aims to describe the characteristics of a pediatric population during the epidemic outbreak in 2023.Population and methods. This cross-sectional study included patients with probable or confirmed dengue fever who were seen from March 13, 2023, to May 19, 2023, in a pediatric hospital in the Autonomous City of Buenos Aires.Results. A total of 112 patients were included. The median age was 12 years; 58% were male. Seventysix percent of them came from the City of Buenos Aires. Twenty-five percent had cohabitants with symptoms compatible with a suspected case. The most frequent clinical manifestations were fever, headache, retro-ocular pain, myalgia, and arthralgia. The most frequent laboratory alterations were leukopenia (65%) and elevated transaminases (60%). Twenty-one percent (24/112) presented alarm signs and required hospitalization. Leukopenia, plateletopenia, and elevated transaminases were associated with the presence of alarm signs. RT-PCR was detected in fifty-three patients; serotype 2 was the most frequent. Twenty-one patients had positive NS1 tests, 18 patients had positive IgM, and 20 patients with clinical and epidemiological links were assumed to be probable dengue cases. There were no cases of severe dengue.Conclusion. Early clinical suspicion and recognition of laboratory parameters associated with alarm signs are essential for an adequate approach to the disease and early supportive treatment during dengue infection.